2005
DOI: 10.2174/0929867054367158
|View full text |Cite
|
Sign up to set email alerts
|

Blast from the Past: The Aluminums Ghost on the Lanthanum Salts

Abstract: Hyperphosphatemia is a common serious complication of chronic renal diseases, which needs appropriate continuous treatment in order to avoid ominous side effects. Therefore, oral chelating agents able to avoid phosphate absorption by the gut are mandatory. In the past, Aluminium salts, and more recently Calcium and Magnesium salts, and a synthetic resin polyallylamine hydrochloride have been employed, but Aluminium was later abandoned, because it has been a silent killer of many uremic patients, due to subtle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
(17 reference statements)
0
16
0
Order By: Relevance
“…Bone is known to be a major reservoir for divalent and trivalent cationic metals, and the pathophysiological effects of aluminium on bone health are well documented . Bone was therefore one of the key target organs in the safety evaluation of LaC.…”
Section: Overview Of Key Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone is known to be a major reservoir for divalent and trivalent cationic metals, and the pathophysiological effects of aluminium on bone health are well documented . Bone was therefore one of the key target organs in the safety evaluation of LaC.…”
Section: Overview Of Key Studiesmentioning
confidence: 99%
“…Despite the positive safety profile of LaC, established by 17 phase 1–4 clinical studies and 10 years of post‐marketing safety monitoring, questions over the long‐term safety of LaC persist. The historical toxicity of aluminium and the perception that lanthanum is chemically similar to aluminium engendered concerns that lanthanum could show aluminium‐like accumulation and toxicity in the bone and central nervous system . Owing to extensive safety concerns surrounding aluminium‐based phosphate binders, their use in clinical practice is now limited, and non‐aluminium‐based binders are instead favoured .…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that long-term LC treatment is possible provided gastrointestinal events that tend to occur more frequently in the early phase of treatment can be controlled. Another potential safety concern of LC treatment is toxicity in bone, liver, and the central nervous system [11][12][13][14][15]. The long-term safety profile of LC in hemodialysis patients receiving treatment for up to 6 years have been reported and appear to show no evidence of adverse effects on the liver, bone, or the central nervous system [9].…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating the efficacy and safety of LC administration over 2, 3, and 6 years have consistently reported that LC is well tolerated with no evidence of safety-related issues [7][8][9][10]. Despite this evidence supporting its safety, concerns over the long-term safety of LC persist because some reports have suggested the potential risks of lanthanum (La) deposition and toxicity in the gastrointestinal tract, bone, liver, and central nervous system [11][12][13][14][15]. These safety concerns would appear to be at least partially based on the known toxicities of aluminium (Al)-containing P binders (PBs), which were commonly used between 1970 and 1990.…”
Section: Introductionmentioning
confidence: 99%
“…A serious caution to the uniform adoption of lanthanum has been raised, however, because, like aluminum, which ultimately was discontinued because of bone and neurologic toxicity, lanthanum is a rare earth metal. Lanthanum ions are absorbed, although to a minimal extent, in the human gut, whereas its blood concentration is increased 10-fold and bone concentration five-fold after shortterm supplementation in patients with CKD (26). Initial pricing of lanthanum carbonate approximates that of sevelamer at nearly 10 times that of calcium acetate and/or carbonate phosphate binders, foreshadowing yet another market combat between dueling pharmaceutical firms.…”
Section: Predicting the Next Step In The Phosphate Binder Sagamentioning
confidence: 99%